Characterization of ß-Glucans Isolated from Brewer’s Yeast and Dried by Different Methods - Vesna Zechner-Krpan; Iva Gospodarić; Senka Đaković; Lana Sajli; Jelena Filipović-Grčić; Vlatka Petravić-Tominac (Food Technology and Biotechnology, 2010)
Two different procedures have been used for isolation of water-insoluble ß-glucans from brewer’s yeast: alkaline-acidic isolation (AA) and alkaline-acidic isolation with mannoprotein removal (AAM). The obtained ß-glucans were then dried by air-drying, lyophilization and combination of sonication and spray-drying. ß-Glucan preparations obtained by AA and AAM isolations had similar values of dry mass, total polysaccharides, proteins and organic elemental microanalysis. The mass fractions of ß-glucan in total polysaccharides were significantly affected by different isolation procedures. Fourier transform infrared (FTIR) spectra of all preparations had the appearance typical for (1→3)-ß-D-glucan. Lyophilization and especially air-drying caused a higher degree of agglomeration and changes in ß-glucan microstructure. Sonication followed by spray-drying resulted in minimal structural changes and negligible formation of agglomerates.